2017
DOI: 10.1007/s00167-017-4471-4
|View full text |Cite
|
Sign up to set email alerts
|

Ramp lesions in ACL deficient knees in children and adolescent population: a high prevalence confirmed in intercondylar and posteromedial exploration

Abstract: The prevalence of ACL-associated ramp lesions in children and adolescents is similar to adult populations. A systematic inspection through the intercondylar notch is recommended during ACL reconstruction to make a precise diagnosis. The posteromedial approach is essentially useful for meniscal repair LEVEL OF EVIDENCE: Testing, previously developed diagnostic criteria in a consecutive series of patients and a universally applied "gold" standard, Level I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 26 publications
2
63
0
1
Order By: Relevance
“…Malatray et al found that the prevalence of ACL-associated ramp lesions in children and adolescents is similar to adult populations. 23 Liu et al also found that those younger than 30 years of age had a significantly higher incidence of ramp lesions. 20 The current study also identified several new significant risk factors, including revision ACLR.…”
Section: Risk Factors For Ramp Lesionsmentioning
confidence: 94%
“…Malatray et al found that the prevalence of ACL-associated ramp lesions in children and adolescents is similar to adult populations. 23 Liu et al also found that those younger than 30 years of age had a significantly higher incidence of ramp lesions. 20 The current study also identified several new significant risk factors, including revision ACLR.…”
Section: Risk Factors For Ramp Lesionsmentioning
confidence: 94%
“…20 Another study evaluating 56 pediatric and adolescent patients also reported the sensitivity of MRI to be 23%. 21 In our series, we found that in 80% (12/ 15) of patients RAMP lesion accompanied ACL rupture. We believe that in patients undergoing ACL reconstruction, examining the posterior horn of medial meniscus for the presence of instability is crucially important.…”
Section: Discussionmentioning
confidence: 54%
“…It is known that medial meniscus lesions caused increase in anterior translation of tibia and instability. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]24 ACL ruptures also increase anterior translation of tibia and also increase loading on meniscus by 200%. 25 On the other hand, in patients with total meniscectomy, the load on graft increased by 33 to 50% even when ACL reconstruction was performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ramp lesions may be present in one in six adult patients with ACL injury, and the prevalence of ramp lesions in children with an ACL injury is similar to adults 95. The surgeon should be vigilant to verify the presence or absence of a medial meniscal ramp tear by visualising the posteromedial compartment.…”
Section: Consensus Methodsmentioning
confidence: 99%